The Tourism Village Development by The Agriculture Based - Helvin, Juan (International Research & Development for Human Beings (IRDH), 2024)
The development of agriculture-based tourism villages is an effort to manage existing resources while utilizing resources that are superior commodities in a village. Additionally, the development of agriculture-based villages will have a positive impact on the community as business actors, as it can help improve the economy of the people in the village. This study was conducted to examine the results of research on the development of agriculture-based tourism villages. The data source used in this study was secondary data obtained from previous studies conducted by researchers. The data was obtained through the Google Scholar portal, and based on the results of this study, it was found that the development of a tourist village will have a positive impact on the community and help rural communities in improving their economy.